1977
DOI: 10.1111/j.1432-1033.1977.tb11253.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Cytosolic NADPH Systems and Isocitrate Dehydrogenase Indicator Metabolites during Ureogenesis from Ammonia in Isolated Rat Hepatocytes

Abstract: 1. Citrate, isocitrate and 2-oxoglutarate levels were determined in isolated rat hepatocytes and in particulate and soluble fractions thereof, obtained by the digitonin and silicone oil fractionation technique.2. Calculated from isocitrate/2-oxoglutarate ratios ("indicator metabolite method"), the redox potential of mitochondrial free NADPH is -402 mV, whereas that of the extramitochondrial (cytosolic) space is about 10 mV more positive, -392 mV.3. Addition of ammonia (either as ammonium chloride or from urea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 20 publications
(7 reference statements)
4
40
0
1
Order By: Relevance
“…The mitochondrial free-NAD redox-state (table 2) The data in table 4 shows that the presence of ammonia has no effect on the free-NADP redox-state potential difference (37-38 mV) across the mitochondrial membrane. In similar experiments, Sies et al [23] found that the NADP redox potential difference in the absence of ammonia was 10 mV more negative in the mitochondria, while ammonia addition produced a potential 15 mV more negative in the cytosol. However, Sies et al [23] used cells isolated from fed rats with fixed lactate/pyruvate and /3-hydroxybutyratel acetoacetate ratios in the absence of oleate, which may account for the conflicting data.…”
Section: Methodsmentioning
confidence: 77%
See 2 more Smart Citations
“…The mitochondrial free-NAD redox-state (table 2) The data in table 4 shows that the presence of ammonia has no effect on the free-NADP redox-state potential difference (37-38 mV) across the mitochondrial membrane. In similar experiments, Sies et al [23] found that the NADP redox potential difference in the absence of ammonia was 10 mV more negative in the mitochondria, while ammonia addition produced a potential 15 mV more negative in the cytosol. However, Sies et al [23] used cells isolated from fed rats with fixed lactate/pyruvate and /3-hydroxybutyratel acetoacetate ratios in the absence of oleate, which may account for the conflicting data.…”
Section: Methodsmentioning
confidence: 77%
“…In similar experiments, Sies et al [23] found that the NADP redox potential difference in the absence of ammonia was 10 mV more negative in the mitochondria, while ammonia addition produced a potential 15 mV more negative in the cytosol. However, Sies et al [23] used cells isolated from fed rats with fixed lactate/pyruvate and /3-hydroxybutyratel acetoacetate ratios in the absence of oleate, which may account for the conflicting data. Although the mitochondrial data of Sies et al was calculated at pH 7.0, instead of pH 7.4, the major discrepancy results from their lower isocitrate gradients: 10 and 2 in the absence and presence of ammonia, respectively and a non-equilibrium of aconitase (see table 5).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The concentrations of IC and KG in isolated heart/ liver mitochondria are in the range 0.02-0.2 and 0.2-2 mM, respectively [9,11,40]. The CO, concentration in vivo is about 1.5 mM [53].…”
Section: Directionality Of Nad-and Nadp-icdh In Vivomentioning
confidence: 99%
“…[8] except that the final concentration of digitonin (Sigma, Munchen) was 1.67 mM instead of 2.0 mM. The lower concentration of digitonin in the separation medium was found to give an improved separation, possibly due to a lower cholesterol content in the liver plasma membrane of the phenobarbital-pretreated animals.…”
Section: Hepatocyte Fractionation With the Digitonin Methodsmentioning
confidence: 99%